Distinct C4 sub‐types and C3 bundle sheath isolation in the Paniceae grasses. (27th December 2021) - Washburn, Jacob D.; Strable, Josh; Dickinson, Patrick; Kothapalli, Satya S.; Brose, Julia M.; Covshoff, Sarah; Conant, Gavin C.; Hibberd, Julian M.; Pires, Joseph Chris
Abstract: In C4 plants, the enzymatic machinery underpinning photosynthesis can vary, with, for example, three distinct C4 acid decarboxylases being used to release CO2 in the vicinity of RuBisCO. For decades, these decarboxylases have been used to classify C4 species into three biochemical sub‐types. However, more recently, the notion that C4 species mix and match C4 acid decarboxylases has increased in popularity, and as a consequence, the validity of specific biochemical sub‐types has been questioned. Using five species from the grass tribe Paniceae, we show that, although in some species transcripts and enzymes involved in multiple C4 acid decarboxylases accumulate, in others, transcript abundance and enzyme activity is almost entirely from one decarboxylase. In addition, the development of a bundle sheath isolation procedure for a close C3 species in the Paniceae enables the preliminary exploration of C4 sub‐type evolution.